PSYCHOLOGICAL AND PEDAGOGICAL ASPECT FORMATION OF SOCIO-CULTURAL IDENTITY OF PUPILS OF MOUNTAIN SCHOOLS REGION OF THE UKRAINIAN CARPATHIANS - Chervinska, Inna (Mountain School of Ukrainian Carpaty, 2020)
The article analyzes the theoretical approaches to the phenomenon of socio-cultural identity, identifies the psychological and pedagogical principles of formation of socio-cultural identity of students of mountain schools in the Ukrainian Carpathians. In order to study methodological, conceptual and methodological approaches that reveal different options for characterizing the concept of sociocultural identity in the context of interdisciplinary discourse, the nature of identity due to the need of a growing individual to recognize, among others, successful self-realization. It is noted that on the basis of the analysis of the latest scientific researches it is possible to assert about rather intensive studying of a problem of identity from the point of view of its socioculturality, formation of sociocultural identity of the young person. The aim of the study is to describe the regional features of the process of forming the socio-cultural identity of mountain school students in the context of sustainable development of the Ukrainian Carpathians region. It is emphasized that the convergence of methodological approaches, principles, methods, forms and ideas determines innovative ways to solve the problem of forming the socio-cultural identity of a growing individual in the educational process and extracurricular activities of general secondary education in the mountain region. Emphasis is placed on the process of forming the socio-cultural identity of the individual in modern society, which is a complex and, at the same time, relevant problem that allows a more thorough understanding of the relationship between man and society, man and environment and predict possible options for social processes sociocultural development of personality. The study points out that the issue of studying the essence of socio-cultural identification includes descriptive characteristics of both the individual and the whole social group and serves as a methodological basis for better understanding and explaining the mechanisms of personality structure, individual group consciousness and typical in certain communities of lifestyles, norms and rules of conduct. It is actualized and proved that in modern conditions the formation of socio-cultural identity requires purposeful organizational and pedagogical, coordinating activities of teachers, parents and students.